Trends in deep-water shark fisheries in the Azores - Aguiar, Ana Raquel Batista (2018)
Deep-sea resources have been increasingly exploited, and due to that, several ecosystems and species have been considerably affected. Deep-water sharks populations have been of the most disturbed by practices of unselected fisheries, bycatch and discard, mainly due to their low commercial value. Those practices make deep-water sharks very vulnerable to overfishing given their life-history traits, increasing their extinction risk. With the prohibition of the direct fishery, and implementation of quotas and TACs (Total Allowable Catches) regarding the deep-sea shark landings, the official landings have dramatically decreased after the 1990s. However, the IUU (Illegal, unreported and unregulated) catch has exponentially increased. With the analysis of catch per unit effort (CPUE), the depths, and the mean weight of the individuals over the years for each one of the nine most caught species in the Azores, we produced a descriptive analysis of the effect of fisheries in those species. The results show that some of these species have been suffering from a great fishing pressure, and their populations will be greatly affected in the near future if drastic measures are not taken when it comes to managing their long term sustainability.